1695 Undergraduate Cardiothoracic Surgery: Pumping Up Knowledge and Inspiration with High-Fidelity Simulation. (12th October 2021) - Hirniak, J; Hussein, F; Seyedzenouzi, G; Adil, S; Vaghela, M; Liu, G; Asif, A; Churchill, T; Zargaran, A
Abstract: Introduction: Alongside declining ST3 applications, cardiothoracic surgery (CTS) is underrepresented in the medical curriculum with 90% of medical students reporting no exposure to the specialty in medical school placements. This may result in clinicians having difficulties recognising emergency presentations, with subsequent referrals made inappropriately. Method: A simulation course involving teaching around common CTS conditions and procedures was delivered by CTS trainees to undergraduate medical students (n = 50). This involved both theory and high-fidelity simulations of coronary anastomoses using cardiac surgical equipment on porcine hearts and ureters. Delegates were given pre and post-test questionnaires, and another at six-weeks to test knowledge retention. Results were statistically analysed using paired and independent sample t-tests. Results: Delegates demonstrated significant improvements in post-test knowledge of 56% ( p <0.01), and sustained improvement of 51% ( p <0.01) six-weeks later compared to baseline. 64% of delegates reported an increased interest in pursuing CTS as a career; 40% reported improved confidence performing a coronary anastomosis. Conclusions: Immediate and long-term knowledge retention of key CTS concepts and ability to assess common CTS pathological scenarios were demonstrated in this study. CTS simulation therefore represents an effective mechanism by which key concepts can be taught to undergraduate medical students, whilst enhancing interest in pursuing CTS as a career. As an educational adjunct, simulation can help bridge the gap between taught theory and applied practice, with the potential to empower future doctors to make more informed referrals and management decisions.